Widespread supplement intake and use of poor quality information in elite adolescent swiss athletes - Mettler, S.; Lehner, G.; Morgan, G. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
Compared with adult athletes, rather little is known about supplementation behavior in adolescent athletes. This study`s aim was to determine elite adolescent athletes` supplement use and sources of information relating thereto. A total of 430 (87%) of 496 questioned athletes returned the anonymized questionnaire. Thereof, 84% consumed at least one weekly supplement and 97% indicated some supplement intake during the previous 4 weeks. On average, 13.3 supplement servings were consumed per week. The 25th, 50th, and 75th percentile was 4.5, 10.5, and 20.0 servings per week, with a maximum of 67. The most prevalent supplements in use were multimineral products (41% of all athletes), multivitamins (34%), Vitamin C (34%), and Vitamin D (33%). Male athletes consumed significantly more Vitamin C and D, sports drinks, protein powder, and recovery products compared with female athletes; whereas, women consumed more iron supplements. The three most important motives for supplement use were recovery support (40%), health maintenance (39%), and performance enhancement (30%). The most frequent answers to the question "who recommended that you use supplements" were family/friends (36%), a physician (27%), and a trainer/coach (25%). The main three information sources about the supplements in use were the persons who recommended the supplementation (56%), the internet (25%), and information provided by supplement suppliers (11%). A positive doping attitude was associated with the consumption of performance enhancing supplements (p = .017). In conclusion, this study among elite adolescent Swiss athletes indicates a widespread and large-scale use of dietary supplements, which was associated with a low level of information quality.